Weather Information for Tribune - H. D. Bond; J. Slattery (Kansas Agricultural Experiment Station Research Reports, 2018)
Summary of weather for research conducted at the Tribune field location.
Keywords: Tribune weather; 2018 weather; southwest Kansas weather report